2006
DOI: 10.1039/b509586g
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectroscopy and binding constants for first-row transition metal complexes of a DOPA-containing peptide

Abstract: A diverse array of biological systems incorporate 3,4-dihydroxyphenlyalanine (DOPA) into proteins and small molecules for cross-linking and material generation. Marine worm eggshells, sea squirt wound plugs, and marine mussel adhesives may all be formed by combining DOPA-containing molecules with high levels of metals. In order to provide model systems for characterizing these biomaterials, we carried out a study on metal binding to a DOPA-containing peptide. Ultraviolet-visible absorption spectra are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 44 publications
4
104
0
1
Order By: Relevance
“…The initially green solution turned blue and finally red as the catechol-Fe 3þ stoichiometry changed from mono-to bis-to tris-, respectively. Identical shifts in absorbance have been reported elsewhere (17). The relative fractions of the three coordination states, extracted from the absorbance data (see Methods for details), show that the monospecies dominate at pH < 5.6, bisat 5.6 < pH < 9.1, and tris-at pH > 9.1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The initially green solution turned blue and finally red as the catechol-Fe 3þ stoichiometry changed from mono-to bis-to tris-, respectively. Identical shifts in absorbance have been reported elsewhere (17). The relative fractions of the three coordination states, extracted from the absorbance data (see Methods for details), show that the monospecies dominate at pH < 5.6, bisat 5.6 < pH < 9.1, and tris-at pH > 9.1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[19,20] Later on, taking advantage of this strong affinity, catechol derivatives have been widely used for synthesis of Ti IV complexes and even as binding agents for TiO 2 nanoparticles. [21][22][23][24] In this paper, we describe the synthesis of a new ligand H 6 4, which bears a catechol and a diethylenetriaminepentaacetic acid (DTPA) moiety linked together through an amide bond (Scheme 1). The DTPA unit provides a stable chelating environment for Ln…”
Section: A C H T U N G T R E N N U N G (H 2 O) 3 ]mentioning
confidence: 99%
“…We have shown that Fe 3þ binding to DOPA-containing peptides is pH dependent, with binding beginning in acidic solutions, with Fe(peptide) formation observed at pH % 3.5. [16] More basic conditions facilitate greater metal-peptide interactions, with Fe(peptide) 3 forming above pH % 7.5. [16] However, our work with whole protein (molecular weight %100 000) has shown that such metal-DOPA interactions occur more readily, regardless of pH.…”
Section: Experimental Partmentioning
confidence: 99%